1990
DOI: 10.1093/nar/18.23.6889
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the isolated domain II/III ofThermus thermophiluselongation factor Tu with the nucleotide exchange factor EF-Ts

Abstract: The middle and C-terminal domain (domain II/III) of elongation factor Tu from Thermus thermophilus lacking the GTP/GDP binding domain have been prepared by treating nucleotide-free protein with Staphylococcus aureus V8 protease. The isolated domain II/III of EF-Tu has a compact structure and high resistance against tryptic treatment and thermal denaturation. As demonstrated by circular dichroism spectroscopy, the isolated domain II/III does not contain any alpha-helical structure. Nucleotide exchange factor, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…The prokaryotic fragment of EF-Tu, enclosing domain I1 and 111, binds EF-Ts in Thermus thermophilus [41]. This observation is more or less in line with ours, showing binding of EF-1P to the carboxy-terminal part of EF-la.…”
Section: Discussionsupporting
confidence: 90%
“…The prokaryotic fragment of EF-Tu, enclosing domain I1 and 111, binds EF-Ts in Thermus thermophilus [41]. This observation is more or less in line with ours, showing binding of EF-1P to the carboxy-terminal part of EF-la.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, it was demonstrated that a polypeptide consisting of domains I1 and 111 of EF-Tu interacts with EF-Ts (Peter et al, 1990a). We assume therefore that an interaction of domain I with EF-Ts is possible only when a complete polypeptide chain including domain I11 is present.…”
Section: Discussionmentioning
confidence: 92%
“…The preparation of EF-Tu"'"' was described in detail previously (Peter et al, 1990a). It was obtained by digestion of nucleotide-free 7: thermophilus EF-Tu with Staphylococcus ciureus V8 protease and purified by gel permeation chromatography.…”
Section: Purification Of Ef-tu Variantsmentioning
confidence: 99%
See 2 more Smart Citations